Prenatal Diagnosis of Parvovirus B19-Induced Hydrops Fetalis by Chemiluminescence In Situ Hybridization - Musiani, M. (American Society for Microbiology, 1999)
Parvovirus B19 can be transmitted transplacentally from the infected mother to the fetus during pregnancy, and hydrops fetalis, abortion, or stillbirth can result. In our study we explored the use of chemiluminescence in situ hybridization to detect B19 DNA on cord blood cells, amniotic fluid cells, and pleuric fluid cells from several cases of hydrops fetalis. B19 DNA was detected by using digoxigenin-labeled probes immunoenzymatically visualized with the chemiluminescent adamantil-1,2-dioxetane phenyl phosphate substrate for alkaline phosphatase. The luminescent signal emitted from the hybridized probes was detected, analyzed, and measured with a high-performance, low-light-level imaging luminograph connected to an optical microscope and to a personal computer for the quantification and localization of the chemiluminescent emission inside individual cells.